2008
DOI: 10.1017/s0022112008000311
|View full text |Cite
|
Sign up to set email alerts
|

The aeroacoustics of slowly diverging supersonic jets

Abstract: This paper is concerned with utilizing the acoustic analogy approach to predict the sound from unheated supersonic jets. Previous attempts have been unsuccessful at making such predictions over the Mach number range of practical interest. The present paper, therefore, focuses on implementing the necessary refinements needed to accomplish this objective. The important effects influencing peak supersonic noise turn out to be source convection, mean flow refraction, mean flow amplification, and source non-compact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
101
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(101 citation statements)
references
References 30 publications
(55 reference statements)
0
101
0
Order By: Relevance
“…The equation is singular at the radial positionr c whereŪ (r c ) = −ω/k; herer c may be referred to as the 'envelope critical layer' in order to distinguish it from the usual (phase) critical layer r c . A critical layer of the former type appears in certain generalized formulation of acoustic analogy (Goldstein & Leib 2008), where the singularity has to be removed by reintroducing the weak non-parallel effect of the base flow since all other terms are predesignated as sources. In our study, the signature p m is of hydrodynamic nature for r = O(1), and thus viscous effects are at our disposal and can be used to smoothed out the singularity.…”
Section: The Nonlinearly Generated Slowly Breathing 'Mean Field'mentioning
confidence: 99%
“…The equation is singular at the radial positionr c whereŪ (r c ) = −ω/k; herer c may be referred to as the 'envelope critical layer' in order to distinguish it from the usual (phase) critical layer r c . A critical layer of the former type appears in certain generalized formulation of acoustic analogy (Goldstein & Leib 2008), where the singularity has to be removed by reintroducing the weak non-parallel effect of the base flow since all other terms are predesignated as sources. In our study, the signature p m is of hydrodynamic nature for r = O(1), and thus viscous effects are at our disposal and can be used to smoothed out the singularity.…”
Section: The Nonlinearly Generated Slowly Breathing 'Mean Field'mentioning
confidence: 99%
“…Over the course of decades of theoretical development some acoustic analogies have been found to be more useful than others in constructing predictive tools. Goldstein & Leib [1] and Khavaran [2], have shown that fluctuations of velocity are the leading terms in cold jets that need to be modeled to predict far-field sound autocorrelation, arguably the final statistic of interest in this context. When the jet is heated, velocity fluctuations begin to lose dominance and turbulent enthalpy fluctuations and their correlations with the velocity become more important.…”
Section: What To Measure?mentioning
confidence: 99%
“…The Generalized Acoustic Analogy (GAA) 24,26 is an exact rearrangement of compressible Navier-Stokes equations, governing the fluctuations about an arbitrary base flow. Goldstein (2003) 24 discusses various choices for the base flow.…”
Section: Iiib Acoustic Analogy Computationmentioning
confidence: 99%